IRUS-UK: Improving Understanding of the Value and Impact of Institutional Repositories. Issue 1 (18th May 2016) - MacIntyre, Ross; Jones, Hilary
Abstract : Institutional repositories (IRs) are important research management tools that can give increased visibility to the institution's scholarly outputs. Although statistics were previously available through the various repository interfaces, without an agreed standard it was not possible to measure usage across a range of IRs accurately. IRUS-UK is a national aggregation service, containing details of all content downloaded from participating IRs in the United Kingdom. Through collecting raw usage data and processing them into item-level usage statistics IRUS-UK provides comparable and authoritative standards-based data and also acts as an intermediary between UK repositories and other agencies.